Temporal Discrimination of Sub- and Suprasecond Time Intervals: A Voxel-Based Lesion Mapping Analysis - Gooch, Cynthia M.; Wiener, Martin; Hamilton, A. Cris; Coslett, H. Branch (Frontiers in Integrative Neuroscience, 2011)
We used voxel-based lesion-symptom mapping (VLSM) to determine which brain areas are necessary for discriminating time intervals above and below 1 s. VLSM compares behavioral scores of patients that have damage to a given voxel to those that do not on a voxel-by-voxel basis to determine which voxels are critical for the given behavior. Forty-seven subjects with unilateral hemispheric lesions performed a temporal discrimination task in which a standard stimulus was compared on each trial to a test stimulus. In different blocks of trials, standard stimuli were either 600 or 2000 ms. Behavioral measures included the point of subjective equality, a measure of accuracy, and the coefficient of variation, a measure of variability. Lesions of the right middle and inferior frontal gyri were associated with decrements in performance on both durations. In addition, lesions of the left temporal lobe and right precentral gyrus were associated exclusively with impaired performance for subsecond stimuli. In line with results from other studies, these data suggest that different circuits are necessary for timing intervals in these ranges, and that right frontal areas are particularly important to timing.